Signs of Central Hypersensitivity, Stress, and Anxiety following Treatment for Breast Cancer: A Case Control Study - Ivana Leao Ribeiro; Ximena Gálvez González; Diego Lara Torres; Luz Alejandra Lorca; Snehil Dixit; Nicolás Yáñez Benavides; Francisco Ortega Gonzalez (International Journal of Breast Cancer)
Background. With treatment for breast cancer, women treated may present significant sensory abnormalities in the upper extremity. However, there are no conclusive studies that have evaluated pressure pain thresholds (PPT) in the shoulder of postoperated women for breast cancer. The aim of this study was to compare PPT in the shoulder, stress, anxiety, depression symptoms, and quality of sleep among postoperated women for breast cancer (PO group) and asymptomatic women of shoulder pain (control group). Methods. 40 women participated (n=20, PO group, age: average±standard deviation, 49.2±8.3 years; body mass index (BMI): 27.5±3.0 kg/cm2; surgery time: 22.2±34.4 months; n=20, control group, 46.9±8.1 years; BMI: 26.8±3.5 kg/cm2). The PPT was evaluated with a digital algometer at 32 points in the shoulder region and one control point in the tibialis anterior. Stress, anxiety, and depression were evaluated with the Depression, Anxiety and Stress Scale 21 (DASS-21) and the quality of sleep by the Pittsburgh Sleep Quality Index. Results. Significant differences were observed over 1.5 kgf/cm2 in 33 points evaluated (p<0.01) with a small to high effect size (Cliff’s delta range=0.16; 0.92) and higher levels of anxiety and stress in the PO group (anxiety: median [first; third quartile], 5[3; 12.5]; stress: 9.7±4.7 (7.8; 11.8)) in comparison with the control group (anxiety: 2.5[1; 4.8]; stress: 6.7±3.31 (5.2; 8.3), (p<0.05)). No significant differences were found between the groups in depression and sleep quality (p>0.05). Conclusion. Postoperated women for breast cancer present hyperalgesia in the shoulder anterior and posterior region, low PPT in the tibialis anterior, and higher levels of stress and anxiety compared to the control group.